Economic analysis and outcome assessment of clinical breast examination and mammography screening for breast cancer detection among women in Klang, Selangor / Sophia Mohd Ramli - Sophia, Mohd Ramli (2017)
Breast cancer is the most common cause of cancer death among women in Malaysia. Screening for breast cancer are by opportunistic clinical breast examination (CBE) followed by mammogram if breast abnormality is detected, and by mammography screening among women with risk factors. An increasing number of developed countries recommend mammogram screening in the general population. This study aimed to compare economic aspects and outcome of CBE followed by mammogram when breast abnormality is detected, and mammogram only among women with risk factors in Selangor, Malaysia. Methodology: This was an economic analysis and outcome assessment on breast cancer screening comparing CBE followed by mammogram when abnormality is detected, and mammogram only among women with risk factors. The costs were calculated from the provider‘s perspective which was the Ministry of Health Malaysia. Cost items were identified and measured using micro costing applying the activity based costing approach. The output for cost analysis was cost per breast cancer screening. The outcome measured was the number and rate of breast cancer detected. Cost per breast cancer detected was also calculated for each breast cancer screening approach. To calculate outcome of CBE followed by mammogram when abnormality is detected, records of 15,279 women who came to the health clinics for Pap smear screening and CBE were reviewed. Outcome of mammography only among women with risk factors were obtained by reviewing 1,427 records of women attending the mammography screening in a general hospital. The breast cancer status was ascertained from the Selangor Breast Cancer Registry. Results: The cost of CBE and mammography were RM 6.68 (USD 2.11; 1USD=RM3.17) and RM 197.30 (USD 62.26) per screening, respectively. Largest iv proportion of cost of CBE was contributed by cost of staff (61.1%), followed by cost of utilities and communication (20.1%). For cost of mammography, majority was contributed by cost of equipment and furniture (57.0%), followed by cost of staff (29.0%). The rate of breast abnormality detected by CBE was 0.55% (84 women) of which 0.07% (10 women) had breast cancer. For mammography among women with risk factors, abnormality rate was 4.7% (67 women) of which 2.0% (29 women) had breast cancer. Among breast cancer cases detected, 3 (30.0%) women were detected early (stage 1&2), while 7 (70.0%) detected late (stage 3&4) for CBE followed by mammography when breast abnormality detected, while for mammography among women with risk factors, 10 (34.5%) women were in early stage, while 19 (65.5%) were in late stage. Cost per breast cancer detected (excluding treatment costs) for CBE followed by mammogram when abnormality is detected, and of mammogram among women with risk factors were RM 11,864 (USD3, 744) and RM 9,709 (USD 3,064), respectively. Conclusion: The current practice of CBE followed by mammography when abnormality is detected, and mammogram of women with risk factors should be strengthened as the costs of breast cancer detection were relatively cheap. Efforts should be focused on improving the participation rate for CBE and increasing the budget allocation for mammogram for women with breast abnormality and risk factors of breast cancer.